Efektivitas Pembelajaran Mandiri Audiovisual dan Booklet Bantuan Hidup Dasar (BHD) Terhadap Pengetahuan dan Keterampilan Perawat di RSUD Wonosari - Endang Kusuma Wardani; Arif Setyo Upoyo; Galih Noor Alivian (Journal of Bionursing, 2020)
Background: Basic Life Support (BLS) is the key in handling heart failure events. The results of many studies mentioned the decrease in the ability of BLS both aspects of knowledge and skills. That is why the efforts to maintain such knowledge and skills are needed. The purpose of this study is to identify the effectiveness of audiovisual and BLS booklets independent learning on the nurses’ knowledge and skills at Wonosari RSUD. Method: This research used a quasy experimental design with a pre-posttest with a comparison of two groups approach with 42 respondents, consisting of audio visual groups and booklets groups. The sampling technique used is simple random sampling. The research instrument was in the form of questionnaires and observation sheets. The bivariate statistical test used the Wilcoxon and Mann-Whitney test. Result: The results of the research test with the bivariate test after the intervention on knowledge and skills were obtained in the audio-visual group of significance (p <0.001) and in the booklet group (p <0.001). The test results of differences in knowledge and skills between the two groups after the intervention obtained the results of the significance of knowledge (p = 0.816) and skills (p = 0.112). It means that there is no difference between the audio visual group and the booklet. Conclusion: Audiovisuals and booklets are equally effective in increasing BLS knowledge and skills. Key words: audiovisual, booklet, BLS, knowledge, skill.